Assessment and Analysis of Sustainability of the Socio-Economic Development of Amalgamated Territorial Communities of the Region - Khirivskyi , Roman; Cherevko, Heorhii; Yatsiv , Ihor; Pasichnyk, Tymofii; Petryshyn , Liudmyla; Kucher, Lesia (European Journal of Sustainable Development, 2020)
The article supplies assessment and analysis of sustainability of the socio-economic development of amalgamated territorial communities in Lviv region of Ukraine basing on the methodological approach, proposed by the authors and founded on the principal functions, performed by the territorial communities, and on the estimates of the degree of their fulfilment. Those methods suggest use of a set of indices, which express sustainable or unsustainable development of the economic indices and consider their different intention. Referring to the indices of execution of the local budgets of 22 communities in Lviv region, the authors of the research assess the socio-economic situation of amalgamated territorial communities. Results of the calculations confirm the sufficient sustainability of the socio-economic development of amalgamated territorial communities in Lviv region. However, in 2018, the communities had trouble in executing their socio-economic budgets. The best results of development of the socio-economic indices were demonstrated by Babyna ATC, Davydiv ATC and Zabolottsi ATC, the worse ones – by Biskovychi ATC, Hrabovets ATC and Novyi Kalyniv ATC. To raise the level of the socio-economic standards of living of the “low-performing” amalgamated territorial communities and to support their sustainable development, the government should supply its assistance. Keywords: sustainability, socio-economic development, amalgamated territorial communities, Lviv region, Ukraine